A comparative study on the expression profile of aquaporin 3(AQP3) gene in the skin fibroblast cells of Barbari and Sirohi breeds of goat - Francis, Femi; ., Ashutosh; Parkunan, Thulasiraman (Indian Journal of Dairy Science, 2020)
Lack of availability of good quality and quantity of water affects the physiology of goats. Goats may adapt to thrive well in water deficit areas by making alterations in the expression of aquaporin (AQP) genes for their efficient water use. The current study was carried out in skin fibroblast cells of Barbari and Sirohi goats. Under in vitro conditions, during different temperatures and osmotic treatments, variations in relative expression of AQP3 genes were observed. At higher temperatures the relative expression of AQP3 genes in Sirohi breed was found to be significantly higher (p<0.01) than Barbari breed. However, during hyperosmotic concentration at normal temperatures the relative expression of AQP3 mRNA was significantly ((p<0.05) increased in both the breeds. During a high temperature combination with hyperosmotic concentration in cell culture of skin fibroblast cells the relative expression of AQP3 mRNA was increased in Sirohi breed (p<0.01) whereas it decreased in Barbari goat’s breed. The variations in AQP3 gene expression during water stress condition and during hyperosmotic concentrations of skin fibroblasts cell culture suggests the positive involvement of AQP3 gene in maintaining the water balance in the body.